Drought-tolerant rhizobacterial consortia enhance grapevine growth and tolerance to water deficit - Canavera, Ginevra; Bellotti, Gabriele; Tiwari, Harsh; Frioni, Tommaso; Puglisi, Edoardo (Frontiers in Plant Science, 2026)
In both natural ecosystems and in agroecosystems, Plant Growth-Promoting Rhizobacteria (PGPR) significantly contribute to plant development and stress mitigation through diverse mechanisms. In recent times, their application as microbial biostimulants (MBs) has gained attention, particularly for alleviating drought stress, which increasingly threatens grapevine productivity in both modern and traditional wine-growing regions. Despite this interest, functionally validated and biosafe PGPR consortia specifically tailored for grapevine remain limited. This study isolated drought-tolerant PGPRs from grapevine rhizosphere cultivated under contrasting environmental conditions and experiencing midday leaf water potentials between −1.3 and −1.4 MPa. The isolates were ranked according to their Plant Growth-Promoting Traits (PGPTs), and whole-genome sequencing was performed on the nine most promising strains to evaluate their functional potential and biosafety. Such functional traits are known to influence plant performance, providing a conceptual basis for evaluating their effects on grapevine growth. Based on their complementary PGPT profiles and demonstrated compatibility, these strains were assembled into four bacterial consortia (BC1–BC4). The consortia were applied by root dipping and soil inoculation to one-year-old grapevines subjected to progressive drought stress, in order to assess their potential synergistic effects on plant growth. Treated vines were compared to a non-inoculated control (NI). Results indicate that while BC1 and BC2 did not significantly impact shoot growth, BC3 and partially also BC4 increased shoot length by 35.5% and 26.5%, respectively, compared to NI. Notably, BC3 enhanced shoot elongation during the early phase under well-watered conditions, whereas BC4 conferred greater benefits under water deficit. After five days of suspended irrigation, BC4-treated vines maintained higher photosynthetic activity and stomatal conductance compared to all other treatments, which, displayed almost complete stomatal closure. This response may be linked to the enrichment of indole-3-acetic acid-producing and exopolysaccharide-forming strains, which are known to modulate plant growth and water status. Finally, both BC3 and BC4 promoted greater root biomass by the end of the pot trial. Overall, the results highlight the potential of rationally tailored PGPR consortia to enhance grapevine growth under both optimal and drought conditions, supporting their application as context-specific MBs for sustainable viticulture.